Efficient Chemoenzymatic Synthesis of (RS)-, (R)-, and (S)-Bunitrolol - Banoth, Linga; Chandarrao, Bhukya; Pujala, Brahmam; Chakraborti, Asit K.; Banerjee, U. C. (Synthesis, 2014)
A new chemical and the first chemoenzymatic synthesis of β-adrenergic receptor blocking agent bunitrolol is reported in racemic (RS) and enantioenriched forms (R and S). The intermediates (R)- and (S)-1-chloro-3-(2-cyanophenoxy)propan-2-ol intermediates were synthesized from the corresponding racemic alcohol through enzymatic kinetic resolution. The commercial available lipases PS-C and CCL exhibited complementary enantioselectivity during transesterification of the racemic alcohol with vinyl acetate affording the (R)-alcohol along with (S)-acetate and the (S)-alcohol along with (R)-acetate, respectively, and represent an example of enzymatic switch for reversal of enantioselectivity. The effects of various reaction parameters, such as temperature, time, substrate and enzyme concentration, and reaction medium, on the activity and enantioselectivity were optimized. The (R)- and (S)-alcohols were converted into (S)-and and (R)-bunitrolol, respectively, by treatment with tert-butylamine. The (R)- and (S)-acetates, obtained enzymatically were deacetylated to the corresponding alcohol by chemical hydrolysis and further converted into (S)-and and (R)-bunitrolol by chemical means. This is the first chemoenzymatic synthesis of both of the enantiomers of the drug. (RS)-, (R)-, and (S)-Bunitrolol were also synthesized following the ‘all chemical’ routes from (RS)-, (R)-, and (S)-epichlorohydrin via the corresponding (RS)-, (S)-, and (R)-2-cyanoglycidyl ether and the (RS)-, (R)-, and (S)-1-chloro-3-(2-cyanophenoxy)propan-2-ol intermediates with improved overall yields and better enantiomeric excesses compared to the reported processes.
Keywords: bunitrolol; biocatalysis; lipase; drug; overall enantioselectivity synthesis